The Influence of Auditor Opinion, Company Size, External Pressure on Fraud Financial Reporting with Industrial Conditions as Intervening Variables - I Kadek Pebri Artana; I Putu Gede Diatmika; Anantawikrama Tungga Atmadja (Universitas Pendidikan Ganesha, 2023)
All manufacturing companies are competing to give the impression that people will not choose similar alternative products other than the company itself, so the company must have a strategy and characteristics that make the company increasingly known to the wider community. This study aims to analyze the influence of auditor opinion, company size, and external pressure on fraudulent financial reporting, by considering industry conditions as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The study population was 25 companies and the study sample consisted of 22 companies, with targeted non-probability sampling techniques. The results showed that auditors' opinions negatively affected fraudulent financial reporting, while company size negatively impacted fraudulent financial reporting. Meanwhile, external pressures have had a positive impact on fraudulent financial reporting. In addition, industry conditions can mediate the relationship between auditors' judgments and fraudulent financial reporting. However, the current state of the industry shows no link between company size and fraudulent financial reporting. The implications of this study emphasize the importance of proper internal supervision and control by companies to prevent and overcome the risk of financial reporting fraud, as well as the importance of strict and credible auditor supervision, and more careful attention to industry conditions that affect the level of financial reporting fraud.